Cellulose nanofiber and carrageenan films infused eugenol for food preservation - Wan Amnin, Wan Yahaya; Nurul Aini, Mohd Azman; Adibi, M. Nor; Noor Fitrah, Abu Bakar; Wan Mohd Faizal, Wan Ishak (EDP Sciences, 2024)
This study explores the physicochemical and antioxidant properties of bio-based polymer films made from semi-refined carrageenan (SRC), plasticized with glycerol, and enhanced with eugenol to inhibit lipid degradation in meat patties. The active films were developed using 2% w/w SRC, 0.9% v/v glycerol, 10% v/v cellulose nanofiber (CNF) as a reinforcing agent, and 0.2% and 0.4% v/v eugenol (Eu). The wettability of the films was evaluated using contact angle analysis, while weight loss was assessed through soil burial degradation over a period of four weeks. Additional tests examined the films’ swelling and transparency properties. Lipid degradation in meat patties was measured using Thiobarbituric Acid Reactive Substances (TBARS). The CNG-0.4%Eu films showed a contact angle of 109.01º and a swelling rate of 93.44%. The antioxidant films successfully delayed lipid oxidation in meat patties, with final TBARS values of 0.768–0.844 mg malondialdehyde per kg of sample. Therefore, the CNG-0.4%Eu formulation demonstrates potential as an alternative food packaging material to extend shelf life.